ANALISIS PENGELOLAAN MODAL KERJA PADA KOPERASI UNIT DESA (KUD) HASRAT JAYA DI KABUPATEN KAMPAR - Nainggolan, Maria .V.; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to determine the management of working capital in the Hasrat Jaya Village Unit Cooperative in Kampar Regency in the 2012-2018 period. The subject in this study was the Hasrat Jaya Village Cooperative Unit and the object of the study was the 2012-2018 financial statements which included items in the balance sheet and results of operations calculations. The data collection method used in this study is documentation. Data analysis methods used in this study are the analysis of the ratio of cash turnover, accounts receivable turnover and inventory turnover. Based on the results of the study note that the management of working capital can be known from the elements of working capital, namely cash turnover, accounts receivable turnover and inventory turnover. Cash turnover is categorized less effective because the average cash turnover is 1.39 times. Receivables turnover is considered ineffective because the average receivable turnover is 0.553 times and below the cooperative health standard. accounts receivable turnover is categorized very effective because the average inventory turnover is 7.90 times and above the cooperative health standard. Keywords: Working Capital Management, Cash Turnover, Receivable Turnover, Inventory Turnover